María Eugenia MATÍA AMOR, "Las dimensiones de la memoria. La poesía de Arcadio Pardo". Valladolid, Universidad de Valladolid, 2018, 260 pp. - Ayuso, César Augusto (Tropelías: Review of Literary Theory and Comparative Literature, 2019)
This paper is a review of the book:The Dimensions of the Memory: The Poetry of Arcardio Pardo.Author: María Eugenia MATÍA AMORValladolid, Universidad de Valladolid, 2018, 260 pp.
Keywords: Poetry; Arcadio Pardo; Contemporary; Creative writing